Intracranial hemorrhage associated with medulla oblongata dysplasia in a premature infant: A case report. Issue 17 (April 2018) - Jiang, Li-Na; Wei, Mei-Chen; Cui, Hong
Abstract: Rationale: Medulla oblongata dysplasia is an extremely rare form of neurodevelopmental immaturity in premature infants. Intracranial hemorrhage in premature infants may be closely related to neurodevelopmental immaturity. Diagnoses: We report a female premature infant who succumbed to intracranial hemorrhage caused by medulla oblongata dysplasia. Patient concerns: The infant was born at 31 weeks gestation. The onset manifestation was symptomatic epilepsy associated with subependymal hemorrhage. Interventions: Levetiracetam and sodium valproate were administered. During the hospitalization, hydrocephalus developed and the intracranial hemorrhage aggravated. Outcomes: The infant died on day 171 after birth. Lessons: Early identification and prompt treatment should be emphasized. Clinicians should be aware of this condition, as it can potentially cause neonatal intracranial hemorrhage.